1986
DOI: 10.1099/00222615-21-2-161
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic composition of an endocarditis-associated isolate of Streptococcus faecalis and identification of its glycoprotein antigens by ligand blotting with lectins

Abstract: Summary. The antigenic composition of an endocarditis-associated isolate of Streptococcus faecalis was studied by immunoblotting of whole cells and cell walls from sodium-dodecyl sulphate polyacrylamide gels on to nitrocellulose and detection with serum from patients and hyperimmune rabbit serum. A major envelope protein antigen of mol. wt 53 x lo3 detected with patient's serum was also present in three urinary strains of Str. faecalis and a laboratory strain of Str. faecalis ss. zymogenes but not in Staphyloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

1988
1988
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 10 publications
(12 reference statements)
1
12
1
Order By: Relevance
“…In addition to GelE and SprE, we also found that the FsrABC system of OG1RF regulates at least one other well-described factor important for OG1RF virulence, namely, EfaA. EfaA is a 37-kDa dominant antigen in infective endocarditis caused by E. faecalis (2,26) and is part of what is predicted to be an ABC-type transporter, with EfaA being the lipoprotein component. efaA is the third gene of the efaCBA operon.…”
Section: Vol 188 2006 Transcriptional Analysis Of Og1rf and A ⌬Fsrbmentioning
confidence: 96%
“…In addition to GelE and SprE, we also found that the FsrABC system of OG1RF regulates at least one other well-described factor important for OG1RF virulence, namely, EfaA. EfaA is a 37-kDa dominant antigen in infective endocarditis caused by E. faecalis (2,26) and is part of what is predicted to be an ABC-type transporter, with EfaA being the lipoprotein component. efaA is the third gene of the efaCBA operon.…”
Section: Vol 188 2006 Transcriptional Analysis Of Og1rf and A ⌬Fsrbmentioning
confidence: 96%
“…The effects of host factors on the expression of potential enterococcal virulence factors have also been examined by several groups. There are numerous lines of evidence for enhancement of expression of such factors by growth in serum (1,2,28,29,38); it is not yet known whether the pheromone signalling mechanism is involved in response to the signalling molecules in serum. Finally, it has been found that several E. faecalis peptides identified as pheromones or inhibitors have neutrophil chemotactic activity (22,55) that appears to function via the N-formyl peptide (F-Met-Leu-Phe) receptor (61) of the neutrophil.…”
Section: Cellular Components Involved In Conjugation As Potential Virmentioning
confidence: 99%
“…6 Group B streptococci were also specifically recognised by the lectins of Lycopersicon esculenturn and Solanum tuberosum, whereas the lectin of Datura stramonium, another solanaceous plant, did not agglutinate group B streptoc~cci.~ Furthermore, the use of the Lotus tetragonolobus lectin in Western blotting indicated the presence of fucosyl residues in the cell walls of Enterococcus faecalis, and lectin probes of wheat germ agglutinin, Concanavalin-A, and soybean agglutinin demonstrated the presence of N-acetylneuraminyl, glucosyl, or mannosyl and N-acetylgalactosaminyl residues on the surface of this species. 8 The usefulness of lectin typing for epidemiological purposes for staphylococci, streptococci, neisseria, campylobacters and enterobacteria has been discussed in several studie~.~~~-'' This report describes the agglutination by 25 different lectins from plants and fungi of 95 clinical isolates of P-haemolytic streptococci of different Lancefield groups and assesses the usefulness of lectin agglutination for epidemiological typing.…”
Section: Introductionmentioning
confidence: 99%